Immunosuppression in Gliomas via PD-1/PD-L1 Axis and Adenosine Pathway - Scheffel, Thamiris Becker; Grave, Nathália; Vargas, Pedro; Diz, Fernando Mendonça; Rockenbach, Liliana; Morrone, Fernanda Bueno (Frontiers in Oncology, 2021)
Glioblastoma is the most malignant and lethal subtype of glioma. Despite progress in therapeutic approaches, issues with the tumor immune landscape persist. Multiple immunosuppression pathways coexist in the tumor microenvironment, which can determine tumor progression and therapy outcomes. Research in immune checkpoints, such as the PD-1/PD-L1 axis, has renewed the interest in immune-based cancer therapies due to their ability to prevent immunosuppression against tumors. However, PD-1/PD-L1 blockage is not completely effective, as some patients remain unresponsive to such treatment. The production of adenosine is a major obstacle for the efficacy of immune therapies and is a key source of innate or adaptive resistance. In general, adenosine promotes the pro-tumor immune response, dictates the profile of suppressive immune cells, modulates the release of anti-inflammatory cytokines, and induces the expression of alternative immune checkpoint molecules, such as PD-1, thus maintaining a loop of immunosuppression. In this context, this review aims to depict the complexity of the immunosuppression in glioma microenvironment. We primarily consider the PD-1/PD-L1 axis and adenosine pathway, which may be critical points of resistance and potential targets for tumor treatment strategies.